Health Care-Seeking Behaviour of Coastal Communities in Banyuwangi, Indonesia: Results of A Cross-Sectional Survey - Susy Katikana Sebayang; Erni Astutik; Desak Made Sintha Kurnia Dewi; Ayik Mirayanti Mandagi; Septa Indra Puspikawati (Universitas Airlangga, 2017)
Introduction: Improving health care-seeking behavior of the coastal communities is a pathway to improve their health. This analysis aims to explore the health care-seeking behavior of the coastal communities in Banyuwangi District to recommend the room for improvement for health promotion and health service improvement for these communities.Method: Data from a cross-sectional survey of metabolic syndrome and mental health conducted in coastal communities in Banyuwangi was used for analysis. Randomly selected participants from a list of members of Family Welfare Development Group (Pembinaan Kesejahteraan Keluarga /PKK) were asked for an interview at corresponding village office in Ketapang, Bangsring, Bulu Agung, Grajagan and Kampung Mandar village. Distribution of health care-seeking behaviors was analyzed individually and where possible were segregated by gender and age.Results: More than half of the coastal communities in Banyuwangi District went to health care service to seek health and 7 out of 10 turned to health care service to seek health for their family members. Women more than men turned to health care service when they or their family members fell ill. Private doctors rather than Puskesmas were more popular. Private midwives were the most popular service for antenatal care (ANC) and delivery. Although there was not a clear increase in health care service utilization over time, we found that contraceptive utilization increased with time.Conclusion: The utilization of health care service in Banyuwangi needs to be more promoted especially for men’s health.